2011
DOI: 10.1007/s12134-011-0179-3
|View full text |Cite
|
Sign up to set email alerts
|

The Nonchalant Migrants: Americans Living North of the 49th Parallel

Abstract: This paper reverses the conventional migration lens to focus on the understudied case of a growing population of Americans in Canada. What motivates these native-born US citizens to migrate; how do they adapt to life north of the 49th parallel; what is the nature of the ties they maintain to their US homeland? Drawing on fieldwork in Ottawa, Toronto, and Vancouver, this paper identifies similarities between Americans and other migrants, but also points to a pervasive attitude of nonchalance as a notable differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The growing scholarship on lifestyle migration has contributed significantly to understanding privileged mobility, but, in actuality, all migrants are aiming to enhance their quality of life. The central distinction that needs to be emphasized is the wide variation in the options available for lifestyle enhancement, the ease with which those options can be pursued, and the attitude underlying the movement-ambivalence, even desperation, in some cases, and relative nonchalance in others [32].…”
Section: Moving Beyond Marginalitymentioning
confidence: 99%
“…The growing scholarship on lifestyle migration has contributed significantly to understanding privileged mobility, but, in actuality, all migrants are aiming to enhance their quality of life. The central distinction that needs to be emphasized is the wide variation in the options available for lifestyle enhancement, the ease with which those options can be pursued, and the attitude underlying the movement-ambivalence, even desperation, in some cases, and relative nonchalance in others [32].…”
Section: Moving Beyond Marginalitymentioning
confidence: 99%
“…The limited prior research on American immigrants in Canada suggested that attention to US politics was compatible with integration into Canadian democracy. Indeed, Americans in Canada were said to feel entitled to take part in both domains (Croucher, 2011). Our findings put a finer point on this characterization.…”
Section: Discussionmentioning
confidence: 60%
“…The limited prior research on the American immigrant population in Canada suggests that migrants' attention to native-country politics does not undercut political incorporation in the Canadian context. The participants in Croucher's (2011) study were said to be "perfectly at ease with and fully entitled to possess and practice citizenship in a country where they did not reside … and to practice simultaneous membership" in two nation-states (126; see also Dashefsky andWoodrow-Lafield, 1992 andMatthews andSatzewich, 2006). Yet while everyday life in Canada is in many respects similar to life in the United States, there is no denying that the two countries differ markedly in their party organizations, governing agendas, federal structure, and formal institutions of representation (Bilodeau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, though, it appears that putting down roots as an immigrant has relatively little effect on partisan belonging as an emigrant (cf. Croucher 2011).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%